1992
DOI: 10.1084/jem.175.6.1589
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T cells in murine acquired immunodeficiency syndrome: polyclonal progression to anergy.

Abstract: SummaryWe have examined the kinetics of changes that occur in the helper T cell subset during murine acquired immunodefidency syndrome, which occurs after infection with the mix of viruses known as BM5. We find that there is expansion of the CD4 T cells by 2 wk, 50% of the CD4 T cells become large as the disease progresses, and the CD4 T cell population is increasingly comprised of cells with a memory/activated phenotype. These effects are apparent by 2 wk postinfection, and the change is nearly complete by 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
52
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 42 publications
10
52
0
Order By: Relevance
“…We have previously reported that following infection with BM5, the entire CD4 ϩ T cell compartment changes phenotype within 6 -8 wk, with the cells acquiring an activated/memory phenotype (L-selectin low , CD45RB low , CD69 high , and CD44 high ) (7). CD4 ϩ T cell numbers increase and there is direct evidence from in vivo bromodeoxyuridine (BrdU) incorporation studies that a large fraction of T cells divide (8).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously reported that following infection with BM5, the entire CD4 ϩ T cell compartment changes phenotype within 6 -8 wk, with the cells acquiring an activated/memory phenotype (L-selectin low , CD45RB low , CD69 high , and CD44 high ) (7). CD4 ϩ T cell numbers increase and there is direct evidence from in vivo bromodeoxyuridine (BrdU) incorporation studies that a large fraction of T cells divide (8).…”
mentioning
confidence: 99%
“…CD4 ϩ T cell numbers increase and there is direct evidence from in vivo bromodeoxyuridine (BrdU) incorporation studies that a large fraction of T cells divide (8). However, despite this polyclonal response, the CD4 ϩ T cell compartment loses the ability to respond in vitro to polyclonal or antigenic stimuli as measured by proliferation or cytokine production (1,7).…”
mentioning
confidence: 99%
See 3 more Smart Citations